2003
DOI: 10.1021/ol0352456
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Induced Circular Dichroism

Abstract: [reaction: see text] Achiral molecules or ions can display induced circular dichroism (ICD) within their absorption bands on association with chiral inducing molecules. The reverse process is equally important, although less appreciated: chiral inducing molecules, such as tartrates, can show significantly differing CD bands in different achiral environments. Therefore true ICD due to achiral molecules can only be demonstrated in the spectral region outside the absorption bands of the chiral inducing molecules.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…4(a) show the typical CD spectrum of HSA with the minimums at 208 and 222 nm. 13 Obviously, this finding is an additional and unequivocal confirmation that diapocynin was complexed with HSA. The near-UV CD spectrum of HSA in the presence or absence of diapocynin was also studied.…”
Section: Interaction Of Diapocynin With Hsa: Induced Circular Dichroimentioning
confidence: 59%
See 1 more Smart Citation
“…4(a) show the typical CD spectrum of HSA with the minimums at 208 and 222 nm. 13 Obviously, this finding is an additional and unequivocal confirmation that diapocynin was complexed with HSA. The near-UV CD spectrum of HSA in the presence or absence of diapocynin was also studied.…”
Section: Interaction Of Diapocynin With Hsa: Induced Circular Dichroimentioning
confidence: 59%
“…To perform that, HSA has binding sites, which are cavities in the protein where the drugs are bound. 13 The appearance of ICD is a quite specific property, since it depends on effective binding between the ligand and the protein and also of a specific alteration in its molecular structure, leading to the conversion of its achiral to chiral conformation, in other words, from an optically inactive to active compound. 11 Diapocynin has a 2,2'-disubstituted-biphenyl moiety; hence, any energy barrier that impedes free rotation around the central single bond between the phenyl rings could provoke the appearance of chirality in this molecule, specifically, axial chirality.…”
Section: Introductionmentioning
confidence: 99%
“…It is known as induced chirality and is experimentally detected by the appearance of a new circular dichroism signal, which originally was not present in the protein or in the free ligand [17]. How proposed by Gawronski and Grajewski there are two different conditions for induction of chirality: induction of a dominating chiral structure of the achiral molecule or induction of a chiral arrangement of the electric dipole transition moments between the relevant chromophores of the achiral (guest) and chiral (host) molecules [26]. Regardless its origin, the induction of chirality by host-guest interaction leads to a new circular dichroism signal, which is known as induced circular dichroism (ICD) and can be useful for studying the interaction between proteins and ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the use of drugs that are well-stablished ligands of site I or II and susceptible to ICD are used to evaluate the effect of the competitor studied compound. For instance, phenylbutazone, diazepam and bilirubin as site markers for site I, II and III, respectively [17, 26, 27] and dansylglycine for site II [28] are all susceptible to ICD. For these reasons, here we aimed to study the features of divanillin as a ligand of bovine serum albumin (BSA).…”
Section: Introductionmentioning
confidence: 99%
“…1 Induced circular dichroism (ICD) is observed when covalent or noncovalent association between a chiral substrate and a UV active, stereodynamic probe favors population of a chiral conformation or configuration of the latter, thus causing a distinct CD output. [2][3][4] The development of conformationally flexible receptors capable of reporting a molecular recognition event upon binding to a substrate provides new avenues for chiroptical analysis. [5][6][7][8][9][10] For example, Rosini and Toniolo demonstrated that the absolute configuration of chiral amino acids, carboxylic acids, and alcohols can be correlated to the ICD output of a covalently linked stereodynamic biphenyl reporter unit.…”
Section: Introductionmentioning
confidence: 99%